The Effect of Working Memory Tra - Marashi, Seyed Mojtaba; Adibi Sadinezhad, Mina (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
Working memory plays an important role in learning since it serves as the buffer between past sensations and future behavior, making it essential to understand not only how we encode and recall sensory information in memory but also how we plan for its upcoming use. This study examined the effect of working memory training on vocabulary recall and retention of Iranian EFL learners using the dual N-back task technique. N-back requires the individual to remember an item that was presented a certain number of items previously. To this end, 50 EFL learners were randomly assigned to the experimental (n = 25) and control (n = 25) groups. The participants were taught 100 English words in 20 sessions. In each session, the experimental group also received a dual n-back task. After the treatment, immediate and delayed vocabulary posttests were administered. The obtained data were analyzed through two-way repeated-measures ANOVA and independent samples t-tests. The results showed that the experimental group outperformed the control group in target words’ recall and retention.